Synonymies and seven new species in Lamiinae from the Neotropical Region (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2019)
Apyratuca Galileo & Martins, 2006 is synonymized with Rosalba Thomson, 1864, and three new species are described: Rosalba contracta, from Ecuador; R. venusta, from Ecuador; and R. skelleyi, from Bolivia. Tethystola alboangulata sp. nov. is described from Trinidad and Tobago, and Blabicentrus similis sp. nov. is described from Panama. Blabicentrus bellus (Galileo & Martins, 2004) is recorded from Panama. The genus Pygmaeopsis Schaeffer, 1908, is transferred to Desmiphorini and Pygmaeopsis apicalis sp. nov. is described from Mexico. Pseudestola maculata sp. nov. is described from Costa Rica and Panama. Desmiphora cucullata Thomson, 1868, is considered a synonym of Desmiphora cirrosa Erichson, 1847.